2021
DOI: 10.1016/s0140-6736(21)00731-5
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer population screening and mortality after long-term follow-up in the UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS): a randomised controlled trial

Abstract: Background Ovarian cancer continues to have a poor prognosis with the majority of women diagnosed with advanced disease. Therefore, we undertook the UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) to determine if population screening can reduce deaths due to the disease. We report on ovarian cancer mortality after long-term follow-up in UKCTOCS.Methods In this randomised controlled trial, postmenopausal women aged 50-74 years were recruited from 13 centres in National Health Service trusts in Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
345
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(358 citation statements)
references
References 30 publications
4
345
0
9
Order By: Relevance
“…Although population screening might be an effective measure to control cancer-caused mortality, the effectiveness of general population screening for women’s cancers needs further validation in the real world. A recent randomized controlled trial in UK showed that annual transvaginal ultrasound screening increased the incidence rate of Stage I/II ovarian and tubal cancer but decreased the incidence rate of Stage III/IV ovarian and tubal cancer, relative to non-screening [ 45 ]. Notably, there was no significant reduction in disease-specific death in annual transvaginal ultrasound screening group, indicating the general population screening for ovarian cancer might be unnecessary at present stage [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although population screening might be an effective measure to control cancer-caused mortality, the effectiveness of general population screening for women’s cancers needs further validation in the real world. A recent randomized controlled trial in UK showed that annual transvaginal ultrasound screening increased the incidence rate of Stage I/II ovarian and tubal cancer but decreased the incidence rate of Stage III/IV ovarian and tubal cancer, relative to non-screening [ 45 ]. Notably, there was no significant reduction in disease-specific death in annual transvaginal ultrasound screening group, indicating the general population screening for ovarian cancer might be unnecessary at present stage [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early detection of ovarian cancer remains a significant analytical challenge and an important clinical need. The development of tests for early detection would allow the impact of earlier detection on disease outcome to be assessed [ 155 ]. If proven to be effective in increasing 5-year survival rates, the implementation of community-based screening programs, similar to those currently available for breast cancer, would dramatically decrease mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer (OC) is the gynecological malignant tumor with the highest fatality rate in the female reproductive system [1,2]. Its lack of obvious pathological features, di culty in early diagnosis and lack of accurate tumor markers are all the reasons for poor prognosis of OC [3].…”
Section: Introductionmentioning
confidence: 99%